Analisa Keuntungan dan Kelayakan Usaha Pengolahan Ikan Asap di Kabupaten Bone Sulawesi Selatan - Rafi Ohorella; Yakub Sulaeman; Toto Hardianto; Muh Soghirun; Nina Wulandari (Journal on Education, 2022)
to meet family needs but has opportunities to develop because it is supported by the availability of abundant fish resources and low production costs. This study aims to analyze the advantages of smoked fish processing carried out by smoked fish processing SMEs in Bone Regency and the feasibility of smoked fish processing businesses to be developed in Bone Regency. This research is a quantitative research conducted using financial analysis to find out the cost, income level, and criteria for income analysis for 2021. The results of this study indicate that the profit from processing smoked skipjack fish is Rp. 8,422,400/month. Financial Analysis Net B/C Ratio for skipjack tuna processing shows the number 1.10, meaning that this business is feasible to develop and the Break Event Unit (Kg) of smoked skipjack tuna is 576.49 units (Kg)/month and the Break Event Sales of smoked skipjack tuna is IDR 6,725,693. 75/month.